The Prognostic Significance of Pedicle Enhancement from Contrast-enhanced MRI for the Further Collapse in Osteoporotic Vertebral Compression Fractures. Issue 22 (15th November 2018) - Hyun, Sung Eun; Ko, Jin Young; Lee, Eugene; Ryu, Ju Seok
Abstract : Study Design: A retrospective observational study. Objective: The aim of this study was to investigate the prognostic significance of contrast-enhanced magnetic resonance imaging (MRI) for detecting pedicle enhancement and predicting future collapse in patients with acute benign osteoporotic vertebral compression fracture (OVCF). Summary of Background Data: Traditional morphological classification regarding compression versus burst fractures cannot accurately anticipate the prognosis of further collapse. Identifying subgroups with a higher risk for further collapse may be beneficial in determining the treatment modality, which should be decided immediately after the injury. Methods: One hundred fourteen patients with benign OVCFs who, at the onset, underwent contrast-enhanced spine MRI between 2003 and 2016 were retrospectively analyzed. Patients were recruited on the basis of predefined inclusion and exclusion criteria. The primary outcome was the compression progression rate; other potential variables included demographic and clinical characteristics, initial compression rates, and kyphotic angles. In addition, other structural abnormalities on MRI were assessed. The compression progression rates were compared according to pedicle enhancement, and the prognostic significance of pedicle enhancement for further collapse were analyzed. Results: Further compression progression rates were significantly higher in the pedicle-enhanced (PE) group than in the nonenhanced (NE) group. Multivariate logistic analysis revealed that pedicle enhancement may be associated with further compression progression ≥10%. The vertebral augmentation (VAG) protective effect against collapse was only significant within the PE group, while bone densitometry and patients' mobility were significant only within the NE group. The log-rank test revealed a statistically significant difference in the rates of further collapse ≥10% during the 1 year between the groups. Conclusion: Sign of pedicle enhancement is a potential risk factor for further compression progression. Contrast-enhanced MRI should be performed at the onset to better determine the future risk of collapse and to choose a better treatment modality for benign OVCF patients. Level of Evidence: 3